Effect of single overload on fatigue crack growth in QSTE340TM steel and retardation model modification. (1st May 2019) - Lu, Yun-chao; Yang, Feng-peng; Chen, Te
Highlights: Overload experiments has been conducted on QSTE340TM sheet steel under four load ratios and three overload ratios. Detailed fatigue crack growth data and crack closure data were obtained. A new effective stress intensity factor according to crack length was proposed based on the closure load and fractography analysis results. A modified model based on both residual stress effect and plasticity-induced crack closure effect was proposed. The predictions of the model showed good agreement with the experimental results. Abstract: To analyze the effect of single tensile overload on fatigue crack growth behavior, a series of experiments have been conducted under different load ratios and overload ratios on QSTE340TM automobile steel. The results showed that the application of overload extended the fatigue life of the specimens in all cases. The fatigue crack growth rate curves presented different patterns between the case load ratio R  = 0.7 and the cases R  = 0.1, 0.3, 0.5. Difference between the trends of the closure load and the fatigue crack growth rate in the cases R  = 0.1, 0.3, 0.5 was found and discussed. The images of fracture surface were obtained by Scanning Electron Microscope. A new effective stress intensity factor expression was proposed and discussed. A combined model based on both the residual stress effect and the plasticity-induced crack closure effect was proposed by modifying the Wheeler model and applying the new effective stress intensity factor expression. The proposed model gave reliable estimates of QSTE340TM steel for all overload cases and two other materials from references.